New species of Crotonia (Acari: Oribatida) from Tasmania Rainforest, and the habitat preferences of Crotoniidae - Colloff, Matthew J. (Zootaxa, 2009)
Two new species of oribatid mite belonging to the genus Crotonia are described from tree trunks and their associated bryophytes in callidendrous rainforest, dominated by Nothofagus cunninghami, in Northeastern Tasmanian: C. tasmaniana sp. nov. and C. pyemaireneri sp. nov. Holonothrus ryszardi Łochyńska, 2008 is designated the junior subjective synonym of Crotonia ovata Olszanowski, 2000, and a supplementary description of the latter species is provided. The apparent arboreal habitat preferences of crotoniid mites are considered. In Tasmanian rainforest, the frequency of occurrence of these mites in moss on bark is higher than in terrestrial habitats, but not significantly so. High rainfall, a closed canopy, a low mean annual temperature and a consequent extensive corticolous and terricolous cover of bryophytes presents a continuum for these mites between ground and above-ground habitats.